The Role of Psychological Empowerment in Mediating the Relationships between Flexible Working Arrangements and Innovative Work Behavior - Indrayanti, Indrayanti (Jurnal Ilmu Perilaku, 2024)
In today's dynamic work environment, the rise of flexible working arrangements and psychological empowerment has sparked a keen fascination with exploring how these new approaches drive employee innovation. This study examines the role of psychological empowerment in mediating the relationship between flexible work arrangements and innovative work behavior. A quantitative approach was used with a cross-functional method. A total of 255 employees in Indonesia took part in the research by filling in instruments via Google Forms. The convenience sampling technique was implemented in this study, focusing on those with at least one year of experience in organizations with hybrid or flexible work designs. Data were analysed using SMART PLS 4.0. The results showed that psychological empowerment fully mediated the relationship between flexible work arrangements and innovative work behavior. These findings suggest that organizations should focus on designing flexible work arrangements that encourage psychological empowerment in individuals, which may ultimately lead to increased innovative work behavior.